EXTRACTION OF ALUMINA FROM BAUXITE RESIDUE FOR PREPARATION OF SYNTHETIC ZEOLITE WITH FERRUM CONCENTRATE AS BY PRODUCT - Aziz, Muchtar (Jurnal Zeolit Indonesia, 2010)
Extraction of alumina from bauxite West Kalimantan (containing 45% of Al2O3 and 16% of Fe2O3) has been conducted, it is produce a alumina and bauxite residue (red mud). The residues were still containing alumina about 20% and ferrum (Fe2O3) about 37%. On further, residues processed through baking or sintering with mixture of soda and lime (lime-soda sinter process) at temperature of 800Â°-1100Â°C. Sintering which dissolved on dilute solution of sodium carbonate, was produces a aluminum hydrate (2NaAlO2) and residue of dissolution. Dipresipitasi solution produces aluminum hydrate precipitate (Al (OH) 3) that can be utilized as a raw material of synthetic zeolite. Ferrum minerals on residues dissolution was concentrated with 1000 gauss magnetic separator that produces a ferrum concentrate as a side effect. The result showed that alumina about 75% to 85% could be extracted or recovered from residues of bauxite with 98.7% of Al2O3, and also it was produced a ferrum concentrate grades 66% of Fe2O3 (46 % Fe) with acquisition of 40% as a side product.